Diagnostic and therapeutic dilemma in Stevens–Johnson syndrome-like acute graft-versus-host disease after liver transplantation: A case report - Hung, Yi-Teng; Chang, Yau-Ren; Wang, Hsuan-Ning; Lee, Wei-Chen; Lee, Chen-Fang; Chen, Chun-Bing (Frontiers in Immunology, 2022)
Background Acute graft-versus-host disease (aGVHD) is a severe and fatal complication after orthotopic liver transplantation (OLT). Clinical manifestations of severe aGVHD can resemble drug-induced Stevens-Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN), and there are also various medications, such as antibiotics and immunosuppressants, used after transplantation, causing a diagnostic dilemma. Furthermore, there have been no standardized diagnostic and therapeutic strategies for OLT-aGVHD due to its rarity. Case summary A 52-year-old man presented with generalized maculopapular eruptions, fever, and pancytopenia one month after OLT and 4 days after taking sulfamethoxazole/trimethoprim. After assessment of the scoring criteria for drug causality of drug allergy, histopathological findings of skin biopsy, lymphocyte activation test of the potential offending drug, and microchimerism study, the diagnosis was in favor of aGVHD mimicking SJS/TEN. Considering severe sepsis, anti-tumor necrosis factor alpha (TNF-α) agent, etanercept, was used to replace tacrolimus and corticosteroid. Skin lesions resolved gradually after anti-TNF-α biologics rescue; tacrolimus and corticosteroid therapy were re-administrated after controlling sepsis. Pancytopenia recovered and the patient was discharged in a stable condition. Conclusion We demonstrated a diagnostic strategy for OLT-aGVHD. Targeting therapy with anti-TNF-α blockade and a temporary withdrawal of traditional immunosuppressants may be among effective and safe therapeutic options of OLT-aGVHD for those with severe sepsis.